The Study Skills Handbook - Cottrell, Stella (Basingstoke : Palgrave Macmillan, 2008)
This title introduces higher-level study skills and allows students to develop a deeper understanding of the learning process itself, encouraging a reflective and well-informed approach to study.
Previous ed.: 2003.
Includes bibliographical references (p. 346-347) and index.
Keywords: Study skills; Education